Response adaptive mechanisms of three mangrove (Avicennia marina, Aegiceras corniculatum, and Bruguiera gymnorrhiza) plants to waterlogging stress revealed by transcriptome analysis - Su, Bo-Yu; Wang, You-Shao; Sun, Cui-Ci (Frontiers in Marine Science, 2022)
Distributing in different elevation of intertidal zone, mangrove plants suffer different periods of flooding and with varied adaptability to waterlogging form the physiological structure to the metabolism mechanism. Associating with species distribution, transcriptome sequencing was performed to explore the interspecific difference of molecular response mechanisms among Avicennia marina, Aegiceras corniculatum and Bruguiera gymnorhiza under waterlogging stress. Results showed that counts of differentially expressed genes (DEGs) in A. marina were highest after the stress, followed by A. corniculatum and B. gymnorhiza. It was found that genes with high differential expression fold (more than 8 folds) in the three plants could be classified into four categories: structural regulation, transport, biosynthesis, and protection. It was also found that A. marina has strong regulation ability in metabolic process, which can guarantee energy supply and maintain active biosynthesis under waterlogging condition. Besides, A. marina activated in ethylene synthesis pathway to promote aerenchyma formation and to avoid root tissue hypoxia. Being different with A. marina and B. gymnorhiza, A. corniculatum down regulated the XET, metK and ACCO genes, which involved in the cell wall regulation or ethylene formation. Alcohol dehydrogenase (ADH) and lactate dehydrogenase (LDH) were cloned from A. marina, A. corniculatum and B. gymnorhiza. The cloned genes were named as AmADH, AmLDH, AcADH, AcLDH, BgADH and BgLDH, respectively. qRT-PCR verified that LDHs and ADHs involved in the response of mangrove plants to waterlogging stress, and interspecific difference was observed. The expressions of AcADH and AcLDH were the most prominent. Combined with transcriptome, it was considered that A. corniculatum was more dependent on the expression of AcADH and AcLDH that can compensate the weakness of cell wall regulation, while the A. marina was more dependent on the regulation of cell structure reversely.